The Effect of Three Coating Materials on the Candidal Growth, on the Surface and Color of A heat-Cure Acrylic Resin Denture Base - Monia MN Kandil; Nadia T Jaffer; Enas Yaseen Shehab (University of Mosul, College of Dentistry, 2009)
Aims: To evaluate the effect of three coating materials: Acrylic resin coating "monopoly", olive oil andgrape seeds oil on the Candida albicans growth, and on color of a heat - cured acrylic resin denture base.Materials and methods: Three coating materials underwent pores method to find out their antifungaleffect. The effect of coating materials on the acrylic denture base surface was determined via Sensitivity testin which twenty discs of acrylic resin 6mm diameter and 2mm thickness were prepared and divided intofour groups: control (uncoated), monopoly, olive, and grape oil coated groups. These discs were added toSabouraud Dextrose agar surface and incubated for 24 hours at 37 oC and the diameter of growth inhibitionzones were measured. Then the Turbidity test was taken place, in which 60 acrylic specimens (1cm x 1cm x2mm) were prepared and immersed in 60 test tubes that were divided into four groups, each group (15specimens) was subdivided into three groups of incubation: 7, 20, and 30 days incubation period, each testtube contained 4 ml Brain Heart Infusion Broth, 0.1 ml of 24 hours Candida albicans, and its correspondingacrylic specimen, turbidity (yeast growth) was measured by a spectrophotometer at 530 nm wave length.For color change measurement test, 20 acrylic resin specimens (45 x 10 x 2.5 mm) were prepared anddistributed into four studied groups. The absorbed light was measured by spectrophotometer and termedoptical density at 345 nm. Results: All coating materials were fungicidal in pores method. Statisticalanalysis of sensitivity test showed that Candida albicans was susceptible at highest extent to monopolycoated denture base followed by the oils coated groups. In turbidity test, monopoly specimens showedantifungal activity in all periods of incubation, but the effect decreased gradually, olive and grape oil coatedspecimens exhibited their highest antifungal activity after 30 days incubation. Color change measurementsshowed that monopoly coated group had the highest optical density, while the olive and grape groupsshowed a decrease in the optical density when compared to uncoated group. Conclusions: Use of coatingmaterials on the acrylic denture base surface was beneficial, especially monopoly in terms of antifungalactivity against Candida albicans followed by natural oils (olive and grape oils). However, coatingmaterials showed a significant change in the color of acrylic denture base.